In vivo reduction of biofilm seeded on orthopaedic implants: safety and efficacy of portable electromagnetic induction heating - Enrique Cordero García-Galán; Marina Medel-Plaza; José J. Pozo-Kreilinger; Héctor Sarnago; Óscar Lucía; Alicia Rico-Nieto; Jaime Esteban; Enrique Gomez-Barrena (Bone & Joint Research)
Aims: Electromagnetic induction heating has demonstrated in vitro antibacterial efficacy over biofilms on metallic biomaterials, although no in vivo studies have been published. Assessment of side effects, including thermal necrosis of adjacent tissue, would determine transferability into clinical practice. Our goal was to assess bone necrosis and antibacterial efficacy of induction heating on biofilm-infected implants in an in vivo setting. Methods: Titanium-aluminium-vanadium (Ti6Al4V) screws were implanted in medial condyle of New Zealand giant rabbit knee. Study intervention consisted of induction heating of the screw head up to 70°C for 3.5 minutes after implantation using a portable device. Both knees were implanted, and induction heating was applied unilaterally keeping contralateral knee as paired control. Sterile screws were implanted in six rabbits, while the other six received screws coated with Staphylococcus aureus biofilm. Sacrifice and sample collection were performed 24, 48, or 96 hours postoperatively. Retrieved screws were sonicated, and adhered bacteria were estimated via drop-plate. Width of bone necrosis in retrieved femora was assessed through microscopic examination. Analysis was performed using non-parametric tests with significance fixed at p ≤ 0.05. Results: The width of necrosis margin in induction heating-treated knees ranged from 0 to 650 μm in the sterile-screw group, and 0 to 517 μm in the biofilm-infected group. No significant differences were found between paired knees. In rabbits implanted with sterile screws, no bacteria were detected. In rabbits implanted with infected screws, a significant bacterial load reduction with median 0.75 Log10 colony-forming units/ml was observed (p = 0.016). Conclusion: Induction heating was not associated with any demonstrable thermal bone necrosis in our rabbit knee model, and might reduce bacterial load in S. aureus biofilms on Ti6Al4V implants. Cite this article: Bone Joint Res 2024;13(12):695–702.